Exosomes Immunity Strategy: A Novel Approach for Ameliorating Intervertebral Disc Degeneration - Li, Weihang; Zhang, Shilei; Wang, Dong; Zhang, Huan; Shi, Quan; Zhang, Yuyuan; Wang, Mo; Ding, Ziyi; Xu, Songjie; Gao, Bo; Yan, Ming (Frontiers in Cell and Developmental Biology, 2022)
Low back pain (LBP), which is one of the most severe medical and social problems globally, has affected nearly 80% of the population worldwide, and intervertebral disc degeneration (IDD) is a common musculoskeletal disorder that happens to be the primary trigger of LBP. The pathology of IDD is based on the impaired homeostasis of catabolism and anabolism in the extracellular matrix (ECM), uncontrolled activation of immunologic cascades, dysfunction, and loss of nucleus pulposus (NP) cells in addition to dynamic cellular and biochemical alterations in the microenvironment of intervertebral disc (IVD). Currently, the main therapeutic approach regarding IDD is surgical intervention, but it could not considerably cure IDD. Exosomes, extracellular vesicles with a diameter of 30–150 nm, are secreted by various kinds of cell types like stem cells, tumor cells, immune cells, and endothelial cells; the lipid bilayer of the exosomes protects them from ribonuclease degradation and helps improve their biological efficiency in recipient cells. Increasing lines of evidence have reported the promising applications of exosomes in immunological diseases, and regarded exosomes as a potential therapeutic source for IDD. This review focuses on clarifying novel therapies based on exosomes derived from different cell sources and the essential roles of exosomes in regulating IDD, especially the immunologic strategy.